HOMICIDE RATES AND HOUSING PRICES IN CALI AND BOGOTÁ, D. C. - Andrés Domínguez (Cuadernos de Economía, 2021)
Currently, the list of most violent cities in the world is dominated by Latin American cities. In 2015, Cali registered 65 homicides per 100,000 inhabitants. In Bogotá, the rate was 17 per 100,000 inhabitants. However, crime is not homogeneously distributed within the urban area, and literature indicates that the local response to crime affects the housing market. The objective of this paper is to estimate the relationship between housing prices and homicide rates in two Colombian cities: Cali and Bogotá. With the use of diverse sources of information and different econometric methodologies, we found that a 10% increase in homicide rates provokes a 2% decrease in housing prices in Cali and 1.8% in Bogotá.